An Evaluation of the Quality of the Desinfection Process in Inanimated Surfaces of Basic Health Units by Biomarkers Research (Revista Brasileira Multidisciplinar, 2013)
Infection Related Health Care – IRHC may occur by exogenous transmission through the contamination of contaminated surfaces. This study aimed at verifying the quality of the process of disinfecting inanimate surfaces of Basic Health Units – BHU in a northeastern city in São Paulo state, through the presence of biomarkers, Staphylococcus aureus and Escherichia coli. We evaluated 7 UBS in random times and days, covering the following areas: dressing-room doorknob, drinking fountains and faucets, office desk, reception counter. Sterile swabs were rubbed on a 20 cm2 surface and transported to the laboratory in Stuart medium to the Clinical Analyses Didactic Laboratory of UNIFEV. The samples were cultured on Blood agar and MacConkey agar at 35 ± 1oC for 24 hours in aerobic and microaerophilic jar, respectively. Staphylococcus aureus was identified by the production of hemolysin, catalase and coagulase. Escherichia coli was identified using the biochemical tests: TSI, citrate, urease, indole, lysine, ornithine and arginine. Of the 105 samples analyzed, 6.66% of the samples were positive for Staphylococcus aureus and Escherichia coli to 2.85%. The Areas which showed the presence of biomarkers were: the reception booth, booth pharmacy, handles of the dressing room, dressing room faucet and drinking fountain. These results corroborate other studies that show that inanimate surfaces are important sources of contamination in the healthcare environment, contributing to crosscontamination and, consequently, to the increase of infection to the patient who is subjected to procedures in this environment. Within this context, government, by means of public health policies, is responsible for the training of health professionals, contributing to the promotion and prevention of public health
Keywords: Staphylococcus aureus; Escherichia coli; Surfaces; IRHA; Biomarker.